Spatial variability of the species composition, abundance, and productivity of the phytoplankton in the White Sea in the late summer period. - Il'yash, L V; Radchenko, I G; Kuznetsov, Leonid L; Lisitzin, Alexander P; Martynova, Daria M; Novigatsky, Alexander N; Chul'tsova, A L (PANGAEA, 2011)
Species composition, cell concentration (N), and biomass (B) of phytoplankton, as well as chlorophyll a (Chl a) concentration, primary production (PP), and concentrations of dissolved inorganic micronutrients (phosphorus, silica, nitrogen as nitrite) were estimated for the Kandalaksha Bay (KB), the Dvina Bay (DB), and the basin (Bas) of the White Sea in August of 2004. Micronutrient concentrations were lower compared to the average long-term values for the summer period. Chl a concentration varies from 0.9 to 2.0 mg/m**3 for most of the studied areas, reaching up to 7.5 mg/m**3 in the Northern Dvina River estuary. The surface water layer of the DB was the most productive area, where PP reached up to 270-375 mg C/m**3/day. Phytoplankton biomass varied from 11 to 205 mg C/m**3 with the highest values observed in the Bas and DB. Three groups of stations were defined during the analysis of phytoplankton species composition similarity. Dinoflagellates Dinophysis norvegica and Ceratium fusus were particular to phytoplankton assemblages in the KB; diatom Ditylum brightwellii was particular to the upper and central parts of the DB. These three phytoplankton species were less abundant in the Bas.
(Table 1) Temperature, salinity, and micronutrient concentrations in the surface water layer of the White Sea on August 17-28, 2004
Keywords: Archive of Ocean Data; ARCOD; Area/locality; CTD, Neil Brown; DEPTH, water; MULT; Nitrite; Phosphate; Professor Shtokman; PSh64; PSh64-02; PSh64-03; PSh64-04; PSh64-05; PSh64-06; PSh64-07; PSh64-08; PSh64-09; PSh64-10; PSh64-11; PSh64-12; PSh64-13; PSh64-15; PSh64-20; PSh64-21; PSh64-25; PSh64-26; PSh64-27; PSh64-36; PSh64-40; Salinity; Silicon; Temperature, water; Wet chemistry; White Sea